Minimally invasive mitral valve repair for functional mitral regurgitation. (20th May 2019) - Girdauskas, Evaldas; Pausch, Jonas; Harmel, Eva; Gross, Tatiana; Detter, Christian; Sinning, Christoph; Kubitz, Jens; Reichenspurner, Hermann
Summary: Systolic heart failure is frequently accompanied by a relevant functional mitral valve regurgitation (FMR) which develops as a direct sequela of the ongoing left ventricular remodelling. The severity of mitral regurgitation is further aggravated by progressive left ventricular enlargement causing leaflet tethering and reduced systolic leaflet movement. The prognosis of such patients is obviously limited by an underlying left ventricular disease, and the correction of secondary FMR has been previously suggested as predominantly 'cosmetic' surgery in the setting of ongoing cardiomyopathy. Inferior results of an isolated annuloplasty in type IIIb FMR supported the philosophy of malignant course of progressive cardiomyopathy and resulted in increasingly restricted indications for mitral valve surgery for FMR in the guidelines. The lack of a standardized pathophysiological approach to correct type IIIb FMR led to the development of valve replacement strategy and edge-to-edge catheter-based mitral valve procedures, which became the most frequent procedures in the FMR setting in Europe. Modern mitral valve surgery combines the advantages of 3-dimensional endoscopic minimally invasive surgical approach with standardized subannular repair to address the pathophysiological background of type IIIb FMR. The perioperative results have been significantly improved, and there is a growing evidence of improved long-term stability of subannular repair procedures as compared to isolated annuloplasty. This review article aims to present the current state-of-the-art of the modern mitral valve surgery in FMR and provides suggestions for future trials analysing the potential advantages in these patients.